Tekniker för kommunikation mellan arbetsfordon: utvärdering av DSRC samt C-V2X - Kjellkvist, Karin; Ahlberg, Tedd (My University, 2019)
In a transport system where vehicles are on their way of becoming autonomous, wireless transmission can be a key factor for success. Information is being shared between vehicles as well as with their surroundings. CPAC Systems in Mölndal, Sweden, are using intervehicular communication as part of their development of control systems for the automotive industry. In the present project, technologies for data transmission are evaluated based on certain criteria, such as latency, range and data rate. The project is a prestudy that lays a foundation for further testing. The evaluated technologies are Dedicated Short Range Communications (DSRC) and Cellular Vehicle-To-Everything (C-V2X). DSRC is recommended when fast data transfer is required and safety has high priority. C-V2X is recommended for data transfer with long distance between units.
Keywords: Elektroteknik och elektronik; Electrical Engineering, Electronic Engineering, Information Engineering